Inorganic composite material, microneedle system containing same and application
By loading the inorganic composite material composed of Fe2N and CeO2 into the microneedle system, reactive oxygen species are generated under ultrasonic activation, solving the problems of inefficiency and resistance of existing antifungal drugs in the treatment of fungal skin infections, and achieving efficient and safe fungal biofilm destruction and killing effects.
Patent Information
- Application Number
- CN202411647438.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
Existing antifungal drugs have problems such as low transdermal efficiency, poor effectiveness, easy formation of drug resistance and fungal biofilm formation when treating fungal skin infections.
Inorganic composite materials composed of Fe2N and CeO2 are used to form Schottky heterojunctions, load them into microneedle systems, and generate a large amount of reactive oxygen species under ultrasonic activation, destroying the fungal biofilm and killing the fungus.
It significantly improves the transdermal efficiency and effectiveness of antifungal treatment, avoids the formation of drug resistance, and effectively destroys fungal biofilms, providing a safe and efficient treatment plan.
Smart Images

Figure BDA0005140015850000091 
Figure HDA0005140015880000011 
Figure HDA0005140015880000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of medical technology, and specifically relates to an inorganic composite material, a microneedle system based on the inorganic composite material, and a preparation method and application thereof. Background Art
[0002] Fungal skin infections (FSIs) are usually caused by pathogenic fungi such as Candida, Cryptococcus and Aspergillus, and are characterized by high morbidity, strong infectivity, and easy recurrence or reinfection. At present, bactericidal drugs represented by fluconazole are the most typical first-line antibacterial drugs in clinical practice. However, with the widespread use of antibiotics, clinical treatment faces treatment difficulties such as low transdermal efficiency, poor antifungal effect, easy formation of drug resistance and fungal biofilm formation. Therefore, there is an urgent need to explore a safe and effective non-antibiotic treatment strategy for FSI.
[0003] As an alternative, sonodynamic therapy (SDT) offers the possibility of a non-invasive approach for the treatment of FSI by generating reactive oxygen species (ROS) under ultrasound irradiation because of its higher tissue penetration depth, non-toxicity, low drug resistance, and minimal side effects. During SDT-induced sonoluminescence, the sonosensitizer absorbs sonoluminescence and excites electrons in the ground state to an excited state. Subsequently, ROS are generated intracellularly through electron transfer or energy transfer, including hydroxyl radicals (·OH), hydrogen peroxide (H2O2), superoxide anion radicals (O2·-), and singlet oxygen ( 1 O2), oxidizing biomolecules such as lipids, proteins and nucleic acids in tumor cells, ultimately leading to cell death. However, inorganic sonosensitizers, including classic titanium dioxide (TiO2) and zinc oxide (ZnO), have low electron-hole separation efficiency and wide band gap, and are prone to electron-hole pair recombination, resulting in low ROS quantum yield under ultrasound irradiation conditions, which greatly limits the application of SDT. Therefore, improving SDT performance remains a key challenge in sonodiodynamics research. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an inorganic composite material and a microneedle system for the treatment of skin bacterial and / or fungal infections, which can effectively solve the problems of low transdermal efficiency, poor effect, easy formation of drug resistance and fungal biofilm formation of existing antibacterial drugs.
[0005] In a first aspect, the present invention provides an inorganic composite material comprising Fe2N and CeO2.
[0006] In some embodiments, there is a Schottky heterojunction between the Fe2N and CeO2.
[0007] In some embodiments, in the inorganic composite material, the CeO2 is a spherical nanoparticle with a depression in the middle.
[0008] In some embodiments, the diameter of the CeO2 is 20-500 nm, for example, 20 nm, 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 300 nm, 400 nm, 500 nm or any value therebetween.
[0009] In some embodiments, the molar ratio of Fe2N to CeO2 is (0.001-1000): 1, preferably (1-100): 1, more preferably (5-50): 1, and further preferably (10-20): 1. In some specific embodiments, the molar ratio of Fe2N to CeO2 is 0.001: 1, 0.005: 1, 0.01: 1, 0.05: 1, 0.1: 1, 0.5: 1, 1: 1, 5: 1, 10: 1, 12: 1, 14: 1, 15: 1, 16: 1, 18: 1, 20: 1, 30: 1, 40: 1, 50: 1, 100: 1, 200: 1, 500: 1, 1000: 1 or any value therebetween.
[0010] In a second aspect, the present invention provides a method for preparing the inorganic composite material according to the first aspect, the preparation method comprising the following steps:
[0011] S3: grinding and second calcining the soluble trivalent iron salt and CeO2 obtained in step S2 to obtain an inorganic composite material including Fe2N and CeO2, wherein the second calcination is performed in an atmosphere containing a nitrogen source.
[0012] Preferably, the CeO2 is obtained by a method comprising the following steps:
[0013] S1: heat treating a solution containing a soluble trivalent cerium salt and polyvinyl pyrrolidone;
[0014] S2: calcining the heat-treated product to obtain CeO2;
[0015] In some embodiments, in step S1, the temperature of the heat treatment is 140-180°C and the time is 5-16h. In some specific embodiments, the temperature of the heat treatment is 140°C, 150°C, 160°C, 170°C, 180°C or any value therebetween. In some specific embodiments, the time of the heat treatment is 5h, 6h, 8h, 10h, 12h, 14h, 16h or any value therebetween.
[0016] In some embodiments, the heat treatment is performed in a forced air drying oven.
[0017] In some embodiments, in step S1, the solution further includes an organic solvent and water.
[0018] In some embodiments, the organic solvent includes ethylene glycol.
[0019] In some embodiments, step S2 further comprises washing and drying the heat-treated product before the first calcination.
[0020] In some embodiments, in step S2, the temperature of the first calcination is 400-600°C, preferably 450-550°C; the time of the first calcination is 0.5-5h, preferably 1-3h. In some specific embodiments, the temperature of the first calcination is 400°C, 450°C, 500°C, 550°C, 600°C or any value therebetween. In some specific embodiments, the time of the first calcination is 0.5h, 1h, 2h, 3h, 4h, 5h or any value therebetween.
[0021] The CeO2 prepared in the method of the present invention is a spherical nanoparticle, which is approximately "bowl-shaped" with a depression in the middle. The bowl-shaped structure can better combine with Fe2N to form an interface structure, and the structure is more stable. Among them, polyvinyl pyrrolidone (PVP) plays an important template role in the synthesis of the inorganic composite material of the present invention, especially in controlling the morphology and size of the CeO2 nanostructure.
[0022] In some embodiments, in step S3, the grinding is performed in a mortar.
[0023] In some embodiments, in step S3, the temperature of the second calcination is 300-600° C., preferably 400-500° C. In some specific embodiments, the temperature of the second calcination is 300° C., 350° C., 400° C., 450° C., 500° C., 550° C., 600° C. or any value therebetween.
[0024] In some embodiments, the second calcination time is 0.5-5h, preferably 1-3h. In some specific embodiments, the second calcination time is 0.5h, 1h, 2h, 3h, 4h, 5h or any value therebetween.
[0025] In some embodiments, the second calcination is performed in an ammonia atmosphere.
[0026] In some embodiments, the soluble trivalent cerium salt includes one or more of cerium nitrate, cerous chloride or cerous sulfate, preferably Ce(NO3)3 or Ce(NO3)3·6H2O.
[0027] In some embodiments, the soluble ferric salt includes one or more of ferric nitrate, ferric chloride or ferric sulfate, preferably Fe(NO3)3 or Fe(NO3)3·9H2O.
[0028] In some embodiments, the molar ratio of the soluble trivalent iron salt to the CeO2 is (0.002-2000):1, preferably (2-200):1, more preferably (10-100):1; further preferably (20-40):1.
[0029] In a third aspect, the present invention provides a microneedle system, comprising a microneedle array, and the inorganic composite material described in the first aspect or the inorganic composite material obtained by the preparation method described in the second aspect filled in the microneedle tips.
[0030] In some embodiments, the microneedle system further comprises a substrate in contact with the microneedle tips.
[0031] In some embodiments, the substrate comprises a biodegradable material.
[0032] In some embodiments, the substrate includes one or more of polyvinyl pyrrolidone, polystyrene, polypeptide, polyamino acid, polyester, polylactic acid, chitin, collagen, gelatin, or methacrylated gelatin.
[0033] In a fourth aspect, the present invention provides a method for preparing the microneedle system according to the third aspect, comprising the following steps:
[0034] (1) mixing an aqueous solution containing the inorganic composite material according to the first aspect or the inorganic composite material obtained by the preparation method according to the second aspect with an aqueous solution containing polyvinyl pyrrolidone to obtain a mixed solution;
[0035] (2) filling a microneedle tip with the mixed solution of step (1) to obtain a microneedle tip containing the inorganic composite material;
[0036] (3) adding a solution containing the substrate material to the microneedle tip obtained in step (2), and drying to obtain the microneedle system.
[0037] In some embodiments, in step (2), the polyvinyl pyrrolidone aqueous solution in the mixed solution can form microneedles after drying to load Fe2N / CeO2 to achieve the purpose of drug loading.
[0038] In some embodiments, in step (2), the mixed solution is filled into the microneedle tip by centrifugation. In some embodiments, the centrifugation conditions include 3000-4000 rpm (e.g., 3000 rpm, 3200 rpm, 3500 rpm, 3800 rpm, or 4000 rpm), 2-8 min (e.g., 2 min, 4 min, 6 min, or 8 min), 20-35° C. (e.g., 20° C., 25° C., 30° C., or 35° C.).
[0039] In some embodiments, in step (3), the substrate material is brought into contact with the microneedle tip by centrifugation. In some embodiments, the centrifugal conditions include 3000-4000 rpm (e.g., 3000 rpm, 3200 rpm, 3500 rpm, 3800 rpm, or 4000 rpm), 2-8 min (e.g., 2 min, 4 min, 6 min, or 8 min), 20-35° C. (e.g., 20° C., 25° C., 30° C., or 35° C.).
[0040] In some embodiments, in step (3), the drying temperature is 20-35°C, and the drying time is 24-60h. In some specific embodiments, the drying temperature is 20°C, 25°C, 30°C, 35°C, or any value therebetween. In some specific embodiments, the drying time is 24h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, or any value therebetween.
[0041] In the fifth aspect, the present invention provides the use of the inorganic composite material described in the first aspect, the inorganic composite material obtained by the preparation method described in the second aspect, the microneedle system described in the third aspect, or the microneedle system obtained by the preparation method described in the fourth aspect in the preparation of a drug for preventing and / or treating bacterial infection and / or fungal infection in a subject.
[0042] In some embodiments, the inorganic composite material or the microneedle system generates reactive oxygen species (ROS) under ultrasound activation, preferably including 1 O2 and OH.
[0043] In some embodiments, the microneedle system is administered transdermally to reach the dermis.
[0044] In some embodiments, the inorganic composite material or the microneedle system destroys bacterial biofilm and / or fungal biofilm under ultrasonic activation to kill bacteria and / or fungi.
[0045] In some embodiments, the conditions for ultrasound activation include: a frequency of 1-5 MHz, a power of 1-5 w / cm 2, the duty cycle is 0%-100%, and the duration is 1-30 min. In some embodiments, the frequency of the ultrasound activation is 1 MHz, 2 MHz, 3 MHz, 4 MHz, 5 MHz or any value therebetween. In some embodiments, the power of the ultrasound activation is 1 w / cm 2 , 2w / cm 2 、3w / cm 2 , 4w / cm 2 , 5w / cm 2 Or any value therebetween. In some embodiments, the duty cycle of the ultrasound activation is 0%, 10%, 20%, 50%, 80%, 100%, or any value therebetween. In some embodiments, the duration of the ultrasound activation is 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, or any value therebetween.
[0046] In some embodiments, the conditions for ultrasound activation include: a frequency of 1-1.5 MHz and a power of 1.5-2 w / cm 2 , the duty cycle is 45-50%, and the duration is 10-20min.
[0047] In some embodiments, the bacteria include one or more of Staphylococcus aureus, Streptococcus pyogenes, or Pseudomonas aeruginosa, and preferably include Staphylococcus aureus.
[0048] In some embodiments, the fungus comprises Candida or Malassezia furfur, preferably comprises Candida albicans.
[0049] In some embodiments, the bacterial infection and / or fungal infection is a skin bacterial infection and / or fungal infection.
[0050] The inventors of the present application have found that the microneedle treatment system based on the inorganic composite material of the present invention has a high degree of safety and is conducive to deep drug delivery. Under the stimulation of ultrasound with high tissue penetration, the inorganic composite material produces reactive oxygen species (ROS), including 1 O2 and ·OH. At the same time, the fungal cell membrane exposed to ROS is directly damaged, the biofilm is destroyed, and Fe2N / CeO2 exhibits a strong bactericidal effect without producing drug resistance. Therefore, the inorganic composite material and its microneedle system of the present invention show broad application prospects in the treatment of skin bacterial and / or fungal infections.
[0051] The inorganic composite material and microneedle system of the present invention can significantly solve the problems of low drug transdermal efficiency, poor effect, easy formation of drug resistance and biofilm formation, improve the economic value of the inorganic composite material and the effect of treating subcutaneous fungal infections, and also provide a theoretical and practical basis for the application of the inorganic composite material in antibacterial aspects. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The electron microscope images of the Fe2N / CeO2 material prepared in Example 1, wherein A is a scanning electron microscope image of the prepared material; B is a transmission electron microscope image of the prepared material; and C is a transmission electron microscope element distribution image of the prepared material.
[0053] Figure 2 This is the XRD spectrum of the Fe2N / CeO2 material prepared in Example 1-2.
[0054] Figure 3 This is the Raman spectrum of the Fe2N / CeO2 material prepared in Example 1-2.
[0055] Figure 4 This is a structural diagram of the MN@Fe2N / CeO2 microneedle prepared in Example 2, wherein A is a schematic diagram of the preparation of the MN@Fe2N / CeO2 microneedle; B is a physical picture of the MN@Fe2N / CeO2 microneedle; and C is a scanning electron microscope image of the MN@Fe2N / CeO2 microneedle.
[0056] Figure 5 Evaluation results of the antibacterial effect of the Fe2N / CeO2-based microneedle system on Candida albicans, where AB is the antibacterial effect display diagram (A) and CFU statistics (B) with increasing Fe2N / CeO2 concentration; CD is the antibacterial effect display diagram (C) and CFU statistics (D) of Fe2N / CeO2 with increasing ultrasound time.
[0057] Figure 6 Evaluation results of the antibacterial effect of Fe2N / CeO2-based microneedle system on Staphylococcus aureus.
[0058] Figure 7 The figures are the evaluation results of the biosafety of the Fe2N / CeO2-based microneedle system in vitro, where A is the effect of the Fe2N / CeO2 microneedle system on the proliferation of L929 cells; and B is the hemolytic activity detection and result statistics of the Fe2N / CeO2 microneedle system.
[0059] Figure 8The results of the evaluation of the therapeutic effect of the Fe2N / CeO2-based microneedle system on the Candida albicans infection model, wherein A is a schematic diagram of the construction of the Candida albicans infection model; B is a diagram of the treatment effect of the Fe2N / CeO2 microneedle system; C is a display of the bacterial mass after treatment with the Fe2N / CeO2 microneedle system; and D is a statistical analysis result of the quality of the bacterial mass after treatment with the Fe2N / CeO2 microneedle system. DETAILED DESCRIPTION
[0060] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0061] In order to solve the problems of low transdermal efficiency, poor effect and easy formation of drug resistance of existing antifungal drugs, the present invention constructs a narrow bandgap Fe2N / CeO2 Schottky heterojunction sonosensitizer and loads it into a microneedle (MN) for sonodynamic therapy (SDT) to treat fungal skin infections (FSI). After pressing on the skin, the microneedle substrate can dissolve into the dermis and release Fe2N / CeO2. The Schottky heterojunction with crystalline-amorphous interface characteristics formed between Fe2N and CeO2 can inhibit the recombination of electron and hole pairs, effectively reduce the energy and band gap required for oxygen activation, and greatly improve the ultrasonic catalytic performance. Therefore, under ultrasonic excitation, a large number of electrons participate in the generation of ROS on the interface, that is, oxygen and water obtain more electrons through high interfacial charge transfer, thereby transforming from the ground state to the excited state, and rapidly generating a large amount of ROS (including 1 O2 and ·OH), promoting bacterial cell damage and biofilm destruction. In addition, CeO2 as a semiconductor material has good electron conduction ability, and the multivalent nature of cerium oxide enables it to better enhance the ultrasonic catalytic performance of the sonosensitizer. The Fenton-like nature of CeO2 can also consume glutathione (GSH) in bacteria, reduce bacterial activity, and further contribute to the sonodynamic method of killing bacteria. In a mouse model of Candida albicans infection, Fe2N / CeO2 showed a significant inhibitory effect on the proliferation of Candida albicans. The present invention not only helps to improve the advancement strategy of SDT, but also provides a unique paradigm for SDT in SFI.
[0062] In some specific embodiments, the method for preparing the inorganic composite material containing Fe2N / CeO2 comprises the following steps:
[0063] Step 1: Weigh Ce(NO3)3·6H2O and polyvinylpyrrolidone (PVP), and completely dissolve them in 75 mL of ethylene glycol and 5 mL of deionized water using a magnetic stirrer. Mix and stir for 20 min.
[0064] Step 2: The mixed and homogenized solution in step 1 was transferred to a 100 ml reaction vessel lined with PTFE and placed in a forced air drying oven at 160°C for 10 h. The cooled sample was washed several times with H2O and ethanol by centrifugation, and then dried in a vacuum oven at 60°C.
[0065] Step 3: Place the dried sample in step 2 into a muffle furnace and calcine at 500° C. for 2 h to obtain a CeO2 sample.
[0066] Step 4: Weigh Fe(NO3)3·9H2O and CeO2 from step 3, put them into a mortar, and grind them thoroughly until mixed. Finally, calcine the ground powder at 450°C for 2h under an ammonia atmosphere. Finally, the reaction product Fe2N / CeO2 is obtained.
[0067] In some embodiments, in the inorganic composite material, the mixing ratio of Fe2N and CeO2 is any different combination.
[0068] In some specific embodiments, the method for preparing the microneedle system comprises the following steps:
[0069] Step 5: Add the Fe2N / CeO2 inorganic composite material obtained in step 4 into deionized water, and mix the two evenly with the help of an ultrasonic stripper (650w, 30min, 25°C) to obtain a Fe2N / CeO2 aqueous solution. Separately weigh polyvinyl pyrrolidone (PVP) and add it to deionized water, mix evenly at room temperature to obtain a PVP aqueous solution.
[0070] Step 6: Add the Fe2N / CeO2 aqueous solution obtained in step 5 to the PVP aqueous solution obtained in step 5, mix well under room temperature reaction conditions, and take an appropriate amount of volume and add it to the microneedle mold. Use centrifugation (3500rpm, 5min, room temperature) to fill the microneedle tip with the mixed solution. Scrape off the excess mixed solution in the non-needle tip part of the microneedle mold to obtain a microneedle tip containing Fe2N / CeO2.
[0071] Step 7: Take the PVP aqueous solution obtained in step 5 and add it to the microneedle tip obtained in step 6. Centrifuge the mold by centrifugation (3500 rpm, 5 min, room temperature) to make the microneedle Fe2N / CeO2 tip in close contact with the PVP substrate.
[0072] Step 8: Place the obtained mixed microneedles in a blue silica gel dryer for drying (room temperature, 48 h), and demold to obtain MN@Fe2N / CeO2 microneedles.
[0073] In some embodiments, the inorganic composite material or the microneedle system can generate reactive oxygen species (ROS) under ultrasound activation, including 1 O2 and OH.
[0074] In some embodiments, the substrate of the microneedle system is any biodegradable material.
[0075] In some embodiments, the substrate of the microneedle system is any biodegradable material, a biocompatible carrier, including but not limited to, polyvinyl pyrrolidone, polystyrene, polypeptide, polyamino acid, polyester, polylactic acid, chitin, collagen, gelatin or methacrylated gelatin and other biodegradable materials. More preferably, the substrate of the microneedle system is PVP.
[0076] In some embodiments, the Fe2N / CeO2-based inorganic composite material and microneedle system are used to prevent and / or skin bacterial and / or fungal infections, by simply pressing the microneedle on the skin to dissolve the biodegradable microneedle tip inside the skin, and then under ultrasound activation, a large amount of ROS (including 1 O2 and ·OH). The microneedle can achieve deep treatment of subcutaneous bacterial infection.
[0077] In some embodiments, the microneedle system can penetrate the skin and reach the dermis.
[0078] In some embodiments, the microneedle system can destroy bacterial biofilms in vitro under ultrasound activation conditions, kill bacteria, and treat bacterial skin infections.
[0079] In some embodiments, the microneedle system can destroy subcutaneous fungal biofilms and kill fungi in vivo under ultrasound activation to treat fungal skin infections.
[0080] In some embodiments, the ultrasonic activation condition is any condition that can activate Fe2N / CeO2.
[0081] Preferably, the ultrasonic activation condition is any condition that can activate Fe2N / CeO2 to generate a large amount of ROS (including 1 O2 and OH).
[0082] Preferably, the conditions for the ultrasound activation include: a frequency of 1-5 MHz and a power of 1-5 w / cm 2 , the duty cycle is 0%-100%, and the duration is 1-30min.
[0083] Preferably, the conditions for the ultrasound activation include: a frequency of 1-1.5 MHz and a power of 1.5-2 w / cm 2 , the duty cycle is 45-50%, and the duration is 10-20min.
[0084] More preferably, the ultrasonic activation conditions are: frequency: 1 MHz; power: 1.5 w / cm 2 ; Duty cycle: 50%; Duration: 15min.
[0085] In some embodiments, the bacteria are any subcutaneous infection bacteria. Preferably, the infection bacteria are one or more of Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa, and related species thereof.
[0086] In some embodiments, the fungus is any subcutaneous infection fungus, such as one or more of Candida albicans, Malassezia furfur, and related species thereof, preferably Candida albicans.
[0087] The reagents and / or kits used in the following examples are all commercially available or can be synthesized by known methods.
[0088] Example 1 Preparation of Fe2N / CeO2 material
[0089] (1) Weigh 2.0 g Ce(NO3)3·6H2O and 1.0 g polyvinylpyrrolidone (PVP) and completely dissolve them in 75 mL ethylene glycol and 5 mL deionized water using a magnetic stirrer. Mix and stir for 20 min.
[0090] (2) The mixed homogenized solution was transferred to a 100 ml reaction vessel lined with PTFE and placed in a forced air drying oven at 160°C for 10 h. The cooled sample was washed several times with H2O and ethanol by centrifugation, and then dried in a vacuum oven at 60°C.
[0091] (3) The dried sample in step (2) was placed in a muffle furnace and calcined at 500°C for 2 h (heating rate of 10°C / min) to obtain a CeO2 sample.
[0092] (4) Accurately weigh 4.04 g (10 mmol) of Fe(NO3)3·9H2O and 60 mg (0.35 mmol) of CeO2 from step (3), put them into a mortar, and grind them thoroughly until mixed. Finally, the ground powder was calcined at 450°C for 2 h (heating rate of 5°C / min) under an ammonia atmosphere. Finally, the reaction product Fe2N / CeO2 was obtained.
[0093] The morphology and composition of the prepared Fe2N / CeO2 particles were characterized by scanning electron microscopy and transmission electron microscopy, and their structure was characterized by XRD and Raman. Figure 1 A to Figure 1 C and Figures 2 to 3 The results show that the present invention successfully prepared an inorganic composite material, referred to as Fe2N / CeO2 material 60.
[0094] Example 2
[0095] The Fe2N / CeO2 material was prepared in a manner similar to Example 1, except that the amount of CeO2 added in step (4) was different, while the mass of Fe(NO3)3·9H2O was the same, see Table 1 below.
[0096] Table 1
[0097]
[0098] Figures 2 to 3 The results of XRD and Raman spectra show that the present invention successfully prepares different Fe2N / CeO2 materials.
[0099] Example 3 Preparation of MN@Fe2N / CeO2 microneedles
[0100] according to Figure 4 A schematic diagram of microneedle preparation, Figure 4 B's MN@Fe2N / CeO2 microneedle, the steps are as follows:
[0101] (1) Take 25 mg of the Fe2N / CeO2 inorganic composite material obtained in Example 1 or Example 2 and add it to 1 mL of deionized water, and mix the two evenly with the help of an ultrasonic stripper (650w, 30min, 25°C) to obtain a Fe2N / CeO2 aqueous solution (25 mg / mL). Separately weigh 0.3 mg of polyvinyl pyrrolidone (PVP) and add it to 1 mL of deionized water, and mix evenly at room temperature to obtain a 30% PVP aqueous solution.
[0102] (2) adding 20 μL of the Fe2N / CeO2 aqueous solution obtained in step (1) to 1 mL of a 30% PVP aqueous solution, and mixing them evenly under room temperature to obtain a mixed solution;
[0103] (3) Take 400 μL of the mixed solution obtained in step (2) and add it to a microneedle mold with a microneedle tip length of 1500 μm. Use centrifugation (3500 rpm, 5 min, room temperature) to fill the microneedle tip with the mixed solution. Scrape off the excess mixed solution in the non-tip part of the microneedle mold to obtain a microneedle tip containing Fe2N / CeO2.
[0104] (4) Take 400 μL of the 30% PVP aqueous solution obtained in step (1) and add it to the Fe2N / CeO2-containing microneedle tip obtained in step (3). Use centrifugation (3500 rpm, 5 min, room temperature) to make the Fe2N / CeO2-containing microneedle tip and the PVP substrate in close contact to obtain a hybrid microneedle.
[0105] (5) The mixed microneedles obtained in step (4) were placed in a blue silica gel dryer for drying (room temperature, 48 h), and demolded to obtain MN@Fe2N / CeO2 microneedles.
[0106] Taking the Fe2N / CeO2 material 60 prepared in Example 1 as an example, Figure 4 The scanning electron microscopy results of C showed that the microneedle tip length was 1000 μm and the MN@Fe2N / CeO2 microneedle was successfully prepared.
[0107] Example 4 Evaluation of the antibacterial effect of Fe2N / CeO2-based microneedle system on Candida albicans
[0108] In order to evaluate the antibacterial ability of Fe2N / CeO2 materials, 500 μL of Candida albicans (SC5314, purchased from Shanghai Shifeng Biotechnology Co., Ltd.) suspension (1×10 6 CFU / mL) were added to a 24-well plate, and further treated with different groups, including different concentrations (0 μg / mL 15.6 g / mL, 31.2 μg / mL, 62.5 μg / mL, ... 1000 μg / mL) of different Fe2N / CeO2 materials prepared in Examples 1 and 2, or ultrasonic treatment for different times (0 min, 0.5 min, 1 min, ... 20 min). The ultrasonic parameters were set to 1.0 MHz, 1.5 W / cm 2 After these treated plates were incubated at 37 °C for 2 h, the C. albicans suspension was diluted to 1:1000, and then 10 μL of the diluted solution was plated on YPD agar medium, incubated at 37 °C overnight, and then the CFU was counted.
[0109] Taking the Fe2N / CeO2 material 60 prepared in Example 1 as an example, the antibacterial results of Candida albicans are as follows: Figure 5 As shown by Figure 5 A and 5B show that as the concentration of Fe2N / CeO2 material increases, the antibacterial effect of Fe2N / CeO2 material gradually increases; Figure 5 C and 5D show that with the increase of ultrasonic time, the antibacterial effect of Fe2N / CeO2 material gradually increases. The above shows that the antibacterial effect of Fe2N / CeO2 material has certain concentration dependence and time dependence.
[0110] Example 5 Evaluation of the antibacterial effect of Fe2N / CeO2-based microneedle system on Staphylococcus aureus
[0111] In order to evaluate the antibacterial effect of Fe2N / CeO2 on Staphylococcus aureus, 500 μL of Staphylococcus aureus (ATCC6538, purchased from Qingdao Haibo Biotechnology Co., Ltd.) suspension (1×10 6 CFU / mL) were added to a 24-well plate, and 500 μg / mL of different Fe2N / CeO2 materials prepared in Example 1-2 were added for ultrasonic treatment. The ultrasonic parameters were set to 1.0 MHz, 15 min, 1.5 W / cm 2 After these treated plates were incubated at 37 °C for 2 h, the S. aureus suspension was diluted to 1:1000, and then 10 μL of the diluted solution was plated on LB agar medium, incubated at 37 °C overnight, and then the CFU was counted.
[0112] Taking the Fe2N / CeO2 material 60 prepared in Example 1 and the Fe2N / CeO2 material 70 prepared in Example 2 as examples, the antibacterial results of the Staphylococcus aureus are as follows: Figure 6 As shown, it shows that Fe2N / CeO2 material also has good antibacterial effect against Staphylococcus aureus.
[0113] Example 6 Evaluation of the biosafety of Fe2N / CeO2-based microneedle system in vitro
[0114] The cytotoxicity of MN@Fe2N / CeO2 patches with different concentrations was evaluated by CCK-8 assay. 4 L929 cells (NCTC clone 929, purchased from Wuhan Punosai Life Science Co., Ltd.) were seeded in 96-well plates at 37°C for 24h. They were then exposed to cell culture medium (DMEM high glucose medium (Thermo Fisher Scientific) + 10% fetal bovine serum (Thermo Fisher Scientific) + 1% penicillin / streptomycin (Solaibao Biotechnology Co., Ltd.)), and the cell culture medium was incubated with different concentrations of MN@Fe2N / CeO2 microneedles prepared in Example 3 for 24h. After 24h, complete culture medium containing 10% CCK-8 was added to the cells at 37°C for 1h, and then the absorbance at 450nm was read using a hybrid multimode reader.
[0115] 1 mL of fresh blood from BALB / c mice (purchased from Shanghai Andor Biotechnology Co., Ltd.) was collected and centrifuged (3000 rpm) for 15 min to obtain red blood cells. After washing with PBS five times, the red blood cell suspension was diluted to 2% (v / v) with PBS and further treated with different groups, including positive group, negative group, MN (30 mg / mL PVP) group and MN@Fe2N / CeO2 (30 mg / mL PVP+500 μg / mL Fe2N / CeO2) group, at 37°C for 3 h. Among them, 2% Triton X-100 was used as a positive control (+), and 20 μL of PBS was used as a negative control (-). After centrifugation at 3000 rpm for 15 min, the supernatant was aspirated and the absorbance of each group at 450 nm was measured using an enzyme marker. The hemolysis rate of these samples was calculated according to the following formula: Hemolysis rate (%) = (ODe-ODn) / (ODp-ODn)×100%. Among them, ODe represents the experimental group, ODn represents the PBS-treated group, and ODp represents 2% of the Triton X-100 group.
[0116] Taking the MN@Fe2N / CeO2 microneedle treatment system prepared by the Fe2N / CeO2 material 60 of Example 1 as an example, the in vitro biosafety evaluation results are as follows: Figure 7 As shown. Figure 7 A and Figure 7 B shows that the MN@Fe2N / CeO2 microneedle treatment system has less toxicity to cells and does not affect the hemolysis rate of cells, and has good biosafety.
[0117] Example 7 Evaluation of the therapeutic effect of Fe2N / CeO2-based microneedle system on Candida albicans infection model
[0118] like Figure 8 As shown in A, a mouse model of subcutaneous infection with Candida albicans was first established. After depilation of the back of male BALB / c mice, Candida albicans (1×10 6 CFU / mL) 100μL. The next day, the mice were randomly divided into 7 groups for treatment, as follows: (1) positive group; (2) control group; (3) control + US (ultrasonic treatment) group; (4) MN (30% PVP) group; (5) MN (30% PVP) + US (ultrasonic treatment) group; (6) MN@Fe2N / CeO2 microneedle group; (7) MN@Fe2N / CeO2 microneedle + US (ultrasonic treatment) group. Among them, 2% Triton X-100 was used as a positive control (+), 20μL PBS was used as a negative control (-), and the conditions for ultrasonic treatment were: 1MHz, 1.2w / cm 2First, the MN@Fe2N / CeO2 microneedles prepared in Example 3 were inserted into the infected area of Candida albicans. After 2 hours, the microneedles were removed and an ultrasonic therapeutic device was used at 1 MHz, 1.2 w / cm 2 , 50% duty cycle for 10 min. The treatment was continued for 3 days and the weight of the mice and the size of the bacterial masses were recorded every day. After 5 days of treatment, the mice were euthanized and their bacterial masses were dissected to detect the size and quality.
[0119] Taking the MN@Fe2N / CeO2 microneedle treatment system prepared by the Fe2N / CeO2 material 60 of Example 1 as an example, the treatment effect evaluation results are as follows: Figure 8 As shown. Figure 8 B- Figure 8 D shows that the Candida albicans infection in mice treated with ultrasound by the MN@Fe2N / CeO2 microneedle therapy system was weakened, the bacterial masses were reduced, and the mass was lightened, which has a significant effect on anti-subcutaneous fungal infection.
[0120] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. An inorganic composite material comprising Fe2N and CeO2, preferably a Schottky heterojunction is formed between the Fe2N and CeO2.
2. The inorganic composite material according to claim 1, characterized in that The molar ratio of Fe2N to CeO2 is (0.001-1000):1, preferably (1-100):1, more preferably (5-50):1; further preferably (10-20):1; In the inorganic composite material, the CeO2 is a spherical nanoparticle with a depression in the middle. Preferably, the diameter of the CeO2 is 20-500 nm.
3. A method for preparing the inorganic composite material according to claim 1 or 2, comprising the following steps: S3: grinding and second calcining the soluble trivalent iron salt and CeO2 to obtain the inorganic composite material, wherein the second calcination is performed in an atmosphere containing a nitrogen source; Preferably, the CeO2 is obtained by a method comprising the following steps: S1: heat treating a solution containing a soluble trivalent cerium salt and polyvinyl pyrrolidone; S2: The heat-treated product is subjected to a first calcination to obtain CeO2.
4. The preparation method according to claim 3, characterized in that: In step S1, the heat treatment temperature is 140-180°C and the time is 5-16 hours; preferably, the heat treatment is carried out in a forced air drying furnace; and / or In step S1, the solution further comprises an organic solvent and water, preferably, the organic solvent comprises ethylene glycol; and / or Step S2 further comprises washing and drying the heat-treated product before the first calcination; and / or In step S2, the temperature of the first calcination is 400-600°C, preferably 450-550°C; the time of the first calcination is 0.5-5h, preferably 1-3h; and / or, In step S3, the temperature of the second calcination is 300-600°C, preferably 400-500°C; the time of the second calcination is 0.5-5h, preferably 1-3h; preferably, the second calcination is carried out in an ammonia atmosphere; and / or, The soluble trivalent cerium salt includes one or more of cerium nitrate, cerous chloride or cerous sulfate, preferably Ce(NO3)3 or Ce(NO3)3·6H2O; and / or The soluble ferric salt includes one or more of ferric nitrate, ferric chloride or ferric sulfate, preferably Fe(NO3)3 or Fe(NO3)3·9H2O; The molar ratio of the soluble trivalent iron salt to the CeO2 is (0.002-2000):1, preferably (2-200):1, more preferably (10-100):1; and further preferably (20-40):
1.
5. A microneedle system comprising a microneedle array, and the inorganic composite material according to claim 1 or 2 or the inorganic composite material obtained by the preparation method according to claim 3 or 4 filled in the microneedle tips.
6. The microneedle system according to claim 5, characterized in that: The microneedle system further includes a substrate in contact with the microneedle tip; Preferably, the substrate comprises a biodegradable material, preferably one or more of polyvinyl pyrrolidone, polystyrene, polypeptide, polyamino acid, polyester, polylactic acid, chitin, collagen, gelatin or methacrylated gelatin.
7. The method for preparing the microneedle system according to claim 5 or 6, comprising the following steps: (1) mixing an aqueous solution containing the inorganic composite material according to claim 1 or 2 or the inorganic composite material obtained by the preparation method according to claim 3 or 4 with an aqueous solution containing polyvinyl pyrrolidone to obtain a mixed solution; (2) filling the microneedle tip with the mixed solution of step (1) to obtain a microneedle tip containing an inorganic composite material; (3) adding a solution containing a base material to the microneedle tip containing the inorganic composite material obtained in step (2), and drying to obtain the microneedle system.
8. The preparation method according to claim 7, characterized in that: In step (2), the mixed solution is filled into the microneedle tip by centrifugation; preferably, the centrifugation conditions include 3000-4000 rpm, 2-8 min, 20-35° C.; and / or In step (3), the substrate material is brought into contact with the microneedle tip by centrifugation; preferably, the centrifugation conditions include 3000-4000 rpm, 2-8 min, 20-35° C.; and / or In step (3), the drying temperature is 20-35° C., and the drying time is 24-60 hours.
9. Use of the inorganic composite material according to claim 1 or 2, the inorganic composite material obtained by the preparation method according to claim 3 or 4, the microneedle system according to claim 5 or 6, or the microneedle system obtained by the preparation method according to claim 7 or 8 in the preparation of a drug for preventing and / or treating bacterial infection and / or fungal infection in a subject.
10. The method according to claim 9, characterized in that The inorganic composite material or the microneedle system generates reactive oxygen species (ROS) under ultrasonic activation, preferably comprising 1 O2 and ·OH; Preferably, the microneedle system is administered transdermally to reach the dermis; Preferably, the inorganic composite material or the microneedle system destroys bacterial biofilm and / or fungal biofilm under ultrasonic activation to kill bacteria and / or fungi; More preferably, the conditions for the ultrasound activation include: a frequency of 1-5 MHz, a power of 1-5 w / cm 2 , duty cycle is 0%-100%, duration is 1-30min; Further preferably, the conditions for the ultrasound activation include: a frequency of 1-1.5 MHz, a power of 1.5-2 w / cm 2 , the duty cycle is 45-50%, and the duration is 10-20min; Preferably, the bacteria include one or more of Staphylococcus aureus, Streptococcus pyogenes, or Pseudomonas aeruginosa, and preferably include Staphylococcus aureus; Preferably, the fungus comprises Candida or Malassezia furfur, preferably comprises Candida albicans; Preferably, the bacterial infection and / or fungal infection is a skin bacterial infection and / or fungal infection.